Hubungan antara dukungan keluarga dengan kesejahteraan psikologis pada petani cengkeh di Desa Sidoasri - Asidiqiah, Putri Nurhikmah; Bantam, Dian Juliarti (Fakultas Psikologi Universitas Hang Tuah, 2025)
Clove farmers who were able to manage their own psychological well-being influenced their work motivation, enabling them to achieve optimal harvest outcomes as expected. One factor that increased psychological well-being was family support. This study aimed to determine the relationship between family support and psychological well-being among clove farmers in Sidoasri Village. Participants were selected using a non-probability sampling method with purposive sampling. The subjects in this study were 100 clove farmers in Sidoasri Village, aged 20 to 68 years, who lived in the same household with their parents, family members, or relatives. Data were collected using a quantitative correlational method, with paper-based tests distributed directly from house to house. This method was used to examine the relationship between variables using scale-based measurements. The instruments employed were a psychological well-being scale modified from Juwita (2024) and a family support scale modified from Kasih (2021). Data were analyzed using Pearson’s product-moment correlation. The findings indicated that the hypothesis was accepted, meaning that there was a positive relationship between family support and psychological well-being among clove farmers in Sidoasri Village.